2005
DOI: 10.1074/jbc.m407816200
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Accessibility of Fluorescent Taxoids Bound at a Paclitaxel Binding Site in the Microtubule Surface

Abstract: The macromolecular accessibility of the paclitaxel binding site in microtubules has been investigated using a fluorescent taxoid and antibodies against fluorescein, which cannot diffuse into the microtubule lumen. The formation of a specific ternary complex of microtubules, Hexaflutax

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 53 publications
4
33
0
1
Order By: Relevance
“…FRETefficiencies from TAMRA-X-taxol to positions on the kinesin head are largely consistent with cryoelectron microscopy structures that show the orientation of bound kinesin heads and that locate bound taxol at or near the luminal surface of the microtubule. The location of the TAMRA-X-taxol is consistent, within experimental uncertainty, with the position of other fluorescent taxol derivatives determined previously (31).…”
Section: Discussionsupporting
confidence: 67%
“…FRETefficiencies from TAMRA-X-taxol to positions on the kinesin head are largely consistent with cryoelectron microscopy structures that show the orientation of bound kinesin heads and that locate bound taxol at or near the luminal surface of the microtubule. The location of the TAMRA-X-taxol is consistent, within experimental uncertainty, with the position of other fluorescent taxol derivatives determined previously (31).…”
Section: Discussionsupporting
confidence: 67%
“…To further examine the effect of HDAC6 function and tubulin acetylation on paclitaxel binding, we did a series of in vitro paclitaxel-binding experiments, using the fluorescent paclitaxel analogue Flutax-2 (17,27,28). These experiments are designed to address the question of whether Flutax-2 has a greater affinity for acetylated microtubules relative to deacetylated microtubules in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…[14,15] From a structural perspective, the paclitaxel-binding site, located in the lumen of the microtubules, [17] is not easily accessible to the paclitaxel molecules in solution. However, it was also shown that paclitaxel binds very quickly to microtubules [18] and that a fluorescent tag attached to paclitaxel bound to microtubules can be recognized by an antibody, [19] which indicates an additional, and external, accessible binding site. This apparent paradox of a hidden but easily accessible luminal binding site was elucidated by the discovery of a new external binding site, [20] to which a covalently binding MSA, cyclostreptin, [12,21] binds before being internalized to the luminal site.…”
Section: Introductionmentioning
confidence: 99%